6 Questions About Blood Pressure: A recent trial recommends a lower blood pressure target to reduce the risk of heart attacks and strokes. A stroke expert interprets the results. Issue 1 (February 2016) - Hiscott, Rebecca
Abstract : Ask Your Doctor: Important questions about lower blood pressure recommendations.